From formula to quotation : a study of intratextuality in the Hebrew text of the Psalms with comparisons from the LXX and Targum - Gauthier, Randall (Old Testament Essays, 2008)
This article examines the use of the Psalms within the Psalms, where intratextual lexical recursion arguably indicates instances of formulaic expression, allusion, rewriting, and even quotation. Several examples from the Hebrew (MT) Psalms illustrate this phenomenon with comparisons from two ancient Jewish translations, the Septuagint and Psalm Targum. From the few examples examined in this article, the translations do not appear to replicate the same intratextual references as those of the MT. Evidence for intentional intratextual connections in the Psalms warrants a more systematic investigation, as this has implications for both form-critical assumptions and studies concerned with the final form of the text.
free